O-099 TEAD4 regulates trophectoderm differentiation upstream of CDX2 in human preimplantation embryos. (6th August 2021) - Stamatiadis, P; Boel, A; Cosemans, G; Van Nieuwerburgh, F; Menten, B; De Sutter, P; Stoop, D; Chuva de Sousa Lopes, S. M; Lluis, F
Abstract: Study question: What is the main pathway regulating trophectoderm (TE) differentiation during pre-implantation development in mouse versus human embryos? Summary answer: TEAD4 is acting upstream of CDX2 and is involved in TE differentiation, as TEAD4-null human embryos exhibit compromised TE lineage differentiation. What is known already: TEAD4 is the earliest transcription factor during early embryo development, required for the expression of TE-associated genes leading to successful TE differentiation and subsequent blastocoel formation in mouse. Functional knock-out studies in mouse, inactivating Tead4 by site-specific recombination have shown that Tead4 -null embryos do not express TE specific genes, including Caudal-Type Homeobox Protein 2 ( Cdx2 ) and GATA Binding Protein 3 ( Gata3 ), but expression of inner cell mass (ICM)-specific genes, remains unaffected. Furthermore, ablation of Tead4 compromises embryonic development and subsequent blastocoel formation in mouse. The role of TEAD4, during human pre-implantation development has not been functionally characterized yet. Study design, size, duration: CRISPR-Cas9 was introduced in mouse zygotes and editing efficiency was evaluated by next-generation sequencing (NGS) on 4.5dpc embryos (n = 55). Developmental kinetics were monitored in CRISPR-Cas9 targeted (n = 83), sham-injected (n = 26) and non-injected media-control (n = 51) mouse embryos. Immunofluorescence analysis was performed in Tead4 targeted (n = 57) and non-injected media-control embryos (n = 94). The same methodology was applied in human donated in vitro matured (IVM) metaphase-II (MII) oocytes, which were CRISPR-Cas9 targeted (n = 74) during ICSI or used as media-Control (n = 33). Participants/materials, setting, methods: A gRNA-Cas9 mixture targeting exon 2 of Tead4 / TEAD4 was microinjected in respectively mouse 2PN (pronuclear) stage zygotes, or human IVM MII oocytes along with the sperm. Generated embryos were cultured in vitro for 4 days in mouse or 6.5 days in human. Embryonic development and morphology were assessed daily, followed by a detailed scoring at the late blastocyst stage. Successful targeting following CRISPR-Cas9 introduction was assessed by immunostaining and NGS analysis of the targeted locus. Main results and the role of chance: In mouse, we confirmed previous findings, as the developmental capacity of Tead4 targeted embryos was significantly reduced starting from the morula stage and blastocyst formation rates were 8.97% in the targeted group, compared to 87.23% in the control and 87.50% in the sham group, respectively. Immunofluorescence analysis of late morula and blastocyst stage embryos confirmed the absence of Tead4, Cdx2 and Gata3, resulting from the successful interruption of the Tead4 locus (n = 57). Exon 2 of TEAD4 was successfully targeted in human. In total, 21 embryos from various developmental stages were successfully NGS analyzed and 90, 48% (19 out of 21) of the embryos carried genetic modifications as a result of CRISPR-Cas9 genome editing and seven blastocysts were identified carrying exclusively frameshift mutations. In contrast to mouse, the developmental capacity of human targeted embryos (25%) did not differ significantly from the control group (23%). However, the blastocyst morphology and quality were compromised in the targeted group showing mostly grade C TE scores, containing very few cells. Immunofluorescence analysis of targeted blastocysts (n = 6) confirmed successful editing by complete absence of TEAD4 and its downstream TE marker CDX2. Limitations, reasons for caution: CRISPR-Cas9 germline genome editing results in multiple editing outcomes with variable phenotypic penetrance, the mosaic nature of which complicates the phenotypic analysis and developmental behaviour of the injected embryos. Wider implications of the findings: Elucidation of the evolutionary conserved molecular mechanisms that regulate self-renewal of the trophoblast lineage can give us fundamental insights on early implantation failure. Trial registration number: Not Applicable